Análise faunística e flutuação populacional de moscas-das-frutas (Diptera: Tephritidae) em cultivos de aceroleira, mangueira e goiabeira em três propriedades no município de Brasil Novo, Pará. - Souza, Alexandra Soares de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2019)
Fruit flies are phytophagous insects that stand out in fruit growing due to impacts on fruits, mainly by the larvae that consume the pulp. The survey of the diversity of these tephritids is still scarce in the country, especially in the Amazon region, so the objective of this work was to survey the biodiversity of fruit flies in the municipality of Brasil Novo, Pará. For studies of faunistic analysis and fluctuation population, tephritid samples were collected weekly with the aid of 18 McPhail traps containing corn protein hydrolyzed protein (Bioanastrepha®), 5% from January 2018 to January 2019, which were distributed in three properties. The frequency, constancy, dominance, abundance, richness, diversity indexes of Shannon-Winner, Simpson and equitability index were evaluated for the faunistic analysis. In addition, the similarity was evaluated using Jaccard and Bray-Curtis coefficients. For the population fluctuation, the monthly fly per trap per day (FTD) index was correlated with the climatic variables: rainfall (mm), mean temperature (°C), and relative humidity (%). Samples of freshly fallen fruits of guava (Psidium guajava), acerola (Malpighia emarginata) and hose (Mangifera indica) were collected during the same period. In the traps 5,849 individuals were obtained, with 12 species identified of Anastrepha nine morphotypes, the species Anastrepha obliqua and Anastrepha striata were super dominant, super abundant, superfrequent and constant in the three study areas, besides these Anastrepha serpentina also stood out one of the properties, diversity indexes were low for all areas, this can be attributed the dominance of A. obliqua e A. striata. The results obtained by the Jaccard and Bray-Curtis coefficients showed that the Bela Vista Site and Chácara Santa Rita presented the highest similarity with abundance and richness of similar species. There was no significant correlation between population fluctuation and climatic variables. In the fruit samples, 7,650 tephritid pupae were obtained, A. obliqua in guava fruits (2.07%), hose (90.26%) and acerola (7.66%) and A. striata on fruits of guava (98.8%) and acerola (1.19%). The following species of parasitoids associated were found in hose and acerola fruits associated with A. obliqua: Aganaspis pelleranoi, Doryctobracon areolatus, Odontosema albinerve, Opius bellus and Utetes anastrephae, and the species associated with A. Striata in guava fruits were A. pelleranoi, D. areolatus, O. albinerve, O.bellus, U. anastrephae and Pachycrepoideus vindemia.
Keywords: Anastrepha; Tritrophic Relationship; Southwest Paraense